(untitled) (Canadian Journal of Counselling and Psychotherapy, 2022)
Recognition of social class as a cultural construct is slowly emerging in the counselling literature. There are prominent social discourses that blame poor individuals for their disadvantage instead of considering the structural causes of poverty. School counsellors must avoid internalizing these beliefs and marginalizing students unintentionally. Social class is often invisible, so youth who are economically disadvantaged may go unnoticed and so may not receive the support they need to overcome systemic barriers and to experience success. The authors invite counsellors to examine and challenge their own biases and assumptions regarding individuals who live in poverty and to work within schools to provide culturally sensitive and socially just leadership. They propose that counsellors adopt the working-class values of openness and honest communication in order to facilitate the formation of therapeutic alliances with youth facing economic disadvantage. The authors highlight salient points from the current literature in order to raise class consciousness and propose advocacy at the micro, meso, and macro levels. They also invite readers to engage in critical reflection on their own beliefs and attitudes about youth who are economically disadvantaged as a foundation for their continued cultural competency development.